Best Practices for Data Management - Bulusu, Lakshman (Oracle Embedded Programming and Application Development, 2011)
Database management using embedded programming languages; design practices for best degree of fitBest practices in terms of connectivity to and interactivity with the Oracle databaseTechniques to connect to multiple databases simultaneously using same metadataBest fit for Oracle in the ADO.NET Framework-ODP.NET, ODE.NETBest practices for data retrievalBest practices for data manipulationBest practices for using LINQ to SQLBest practices for data validationBest practices for using XMLBest practices for handling unstructured dataBest practices to protect data integrity and special cases involvedData: Good, Better, and Bestis the foundation for business information processing, delivery, presentation, in-flight interactivity and querying, and analysis that can be put into action for business operational continuity, better business value, and actionable decision-making. Knowing the data and its business meaning in terms of the usage scope plays a primary role in managing data end-to-end, from source data integration to an unified, consistent, and persistent presentation that enables anytime-anywhere-anyone availability and accessibility. Then follows the task of protecting the data from leakage, breaches, threats, and unauthorized access, both within the enterprise solution domain and beyond the enterprise. Once again, theRightDesign the First Timeis the key driving factor for efficiency of the (enterprise) solution being architected, and goes a long way in promoting optimization, effectiveness, and efficiency of the solution.